PENGARUH SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA PEGAWAI PT. ANGKASA PURA AVIASI - Octaviana , Rahelsa; Maisyarah, Renny (Jurnal Manajemen Dan Akuntansi Medan, 2025)
PT Angkasa Pura II established a subsidiary, PT Angkasa Pura Aviasi, with a focus on managing strategic partnerships at Kualanamu International Airport. PT Angkasa Pura Aviasi is a state-owned enterprise engaged in airport management and airport services. PT Angkasa Pura Aviasi was established based on notarial deed no. 7 dated November 7, 2018, in Tangerang, Banten. The head office of PT Angkasa Pura Aviasi is domiciled in Kualanamu, Deli Serdang, North Sumatra. PT Angkasa Pura Aviasi is a joint venture between PT Angkasa Pura II (Persero) and GMR Airports Consortium. In 2021, the financial information system at PT. Angkasa Pura Aviasi currently uses the Mekari journal application. The use of this system is still relatively new and simple, so it becomes an obstacle in financial recording due to the need to adapt to the new system.